Tissue Doppler echocardiography and outcome in arrhythmogenic right ventricular cardiomyopathy. (1st December 2022) - Hosseini, Sara; Erhart, Ladina; Anwer, Shehab; Heiniger, Pascal S.; Winkler, Neria E.; Cimen, Tolga; Kuzo, Nazar; Hess, Refael; Akdis, Deniz; Costa, Sarah; Gasperetti, Alessio; Brunckhorst, Corinna; et al.
Abstract: Aims: This study aimed at investigating whether tissue Doppler imaging (TDI) is associated with adverse events in arrhythmogenic right ventricular cardiomyopathy (ARVC). Methods and results: Transthoracic echocardiography was performed in 72 patients with definite ( n = 63) or borderline ( n = 9) ARVC diagnosed according to the 2010 Task Force Criteria and included in the prospective Zurich ARVC registry. Myocardial peak systolic tissue velocity (S′) was measured by TDI at lateral tricuspid (tricuspid S′), medial mitral (septal S′), and lateral mitral annulus (lateral S′). Association of echocardiographic parameters with outcome was assessed by univariable Cox regression. During a median follow-up of 4.9 ± 2.6 years, 6 (8.3%) patients died of cardiovascular cause or received heart transplantation and 21 (29.2%) patients developed sustained ventricular arrhythmia. Tricuspid, septal, and lateral S′ were lower in patients who died ( p = 0.001; p < 0.001; p = 0.008; respectively), while tricuspid and septal S′ were lower in those with ventricular arrhythmia ( p = 0.001; p = 0.008; respectively). There was a significant association of tricuspid, septal, and lateral S′ with mortality (HR = 1.61, p = 0.011; HR = 2.15, p = 0.007; HR = 1.67, p = 0.017; respectively), while tricuspid and septal S′ were associated with ventricular arrhythmia (HR = 1.20, p = 0.022; HR = 1.37, p = 0.004; respectively). Kaplan-Meier analyses demonstrated a higher freedom from mortality with tricuspid S′ >8 cm/s ( p = 0.001) and from ventricular arrhythmia with S′ >10.5 cm/s ( p = 0.021). Conclusions: This study demonstrates that TDI provides information on the ARVC phenotype, is associated with adverse events in ARVC patients, and differentiates between patients with and without adverse events. Graphical abstract: Unlabelled Image Highlights: Tissue Doppler tricuspid and mitral annulus velocity useful for assessing ARVC phenotype. Tissue Doppler tricuspid and mitral annulus velocity associated with adverse events in ARVC. Tissue Doppler annulus velocity differentiates patients with and without adverse events in ARVC.